Model for Phosphorus Removal in LD Converter and Design of a Valuable Operative Practice. Issue 5 (5th March 2018) - Mombelli, Davide; Mapelli, Carlo; Barella, Silvia; Gruttadauria, Andrea; Sosio, Roberto; Valentino, Giovanni; Ancona, Vito
Abstract : In the primary ironmaking production process, the use of iron ores featured by a high concentration of phosphorus leads to a greater difficulty to manage the refining period of the hot metal by the Basic Oxygen Furnace. Recently, the phosphorus concentration in the hot metal can reach 0.08–0.11 wt% resulting in operative practice troubles for achieving a final P concentration lower than 0.015 wt%. In this study, a kinetic‐thermodynamic model for dephosphorization is proposed and a more efficient dephosphorization procedure of the hot metal in LD converters (350 t) have been developed. The model is a valuable tool to predict the dephosphorization evolution and allows the implementation of a new blowing pattern, able to reach a final P concentration at the end‐point lower than the threshold value of 0.015 wt% with only a slightly increase in lime (+10%) and oxygen consumption (+3%). Abstract : To face the recently increasing of phosphorus concentration in the hot metal, a kinetic‐thermodynamic model to in‐line control of dephosphorization procedure in LD converters is developed. The model helps the implementation of a new blowing pattern, able to reach the target P concentration at the end‐point with only a slightly increase in lime (+10%) and oxygen consumption (+3%).